Exceptionally high two-photon absorption cross sections in quinoidal diazaacene-bithiophene derivatives - Sauter, Gabriel; Papapostolou, Antonia; Pollien, Audrey; Boschmann, Sergius; Fuchs, Kathleen; Merten, Pascal; Brödner, Kerstin; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F.; Dreuw, Andreas; Tegeder, Petra (Angewandte Chemie. International edition, 2025)
This study addresses the two-photon absorption (2PA) properties of (azaacene-annulated) heterophenoquinones through a synergistic approach combining detailed experimental and theoretical analyses. Exceptionally large 2PA cross sections are found over a broad spectral range in the near-infrared spectral region, with values up to 4100 GM in the 1400-1600 nm range and even higher values of up to 51770 GM in the 850-950 nm range, which is outstanding for organic chromophores of this molecular size. Our quantum chemical calculations support the experimental findings and elucidate the underlying absorption mechanism leading to the corresponding 2PA properties. The occurrence of such large cross sections is explained by the high oscillator strength of the first excited singlet state and its strong coupling to higher excited electronic states. The large (state-to-state) transition dipole moments originate from the acceptor-π-donor-π-acceptor structure of the parent quinoidal bithiophene motif common to all compounds, which in addition also enables their optimal (anti)parallel alignment due to its symmetry and linearity.